Art and alchemy: the mystery of transformation ; [accompanies the Exhibition "Art and Alchemy. The Mystery of Transformation", Stiftung Museum Kunstpalast, Düsseldorf, 5 April - 10 August 2014] - Dupré, Sven; Kerssenbrock-Krosigk, Dedo von (Hirmer, 2014)
"For the first time in Germany, an exhibition spanning all epochs and genres will be introducing the exciting link between art and alchemy in past and present times. 250 works from antiquity to the present, encompassing Baroque art, Surrealism, through to contemporary art from collections and museums in the USA, Great Britain, France, Mexico and Israel reveal the fascination which alchemy exerted for many visual artists. Artists featured in the exhibition, such as Joseph Beuys, Jan Brueghel the Elder, Lucas Cranach the Elder, Max Ernst, Hendrick Goltzius, Rebecca Horn, Anish Kapoor, Yves Klein, Sigmar Polke, Rembrandt van Rijn, Peter Paul Rubens and David Teniers the Younger invite visitors to explore the mystery of transformation"--Publisher's website